Cyclin-dependent kinase 7 (CDK7) expression in human hepatocellular carcinoma: association with HCC progression, prognosis and cell proliferative capacity - Liu, Zheran; Liu, Dajiao; Zhong, Rongrong; Su, Qiuyun; Zhao, Tiancheng; Fu, Fen; Liu, Jinsheng; Xu, Derong; Zeng, Changqing (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: Hepatocellular carcinoma (HCC) is one of the most common malignancies in the world and contributes to a high cancer mortality globally. The multistep progression of HCC is highly related to the activation of oncogenes and the deactivation of cancer suppressor genes. The cyclin-dependent kinase 7 (CDK7) gene is responsible for maintaining a normal cell cycle, acting as a gatekeeper, and plays an important part in RNA transcription. Although previous studies demonstrate that CDK7 is highly expressed in multiple cancers and is associated with the progression and prognosis of these cancers, the potential role of CDK7 in HCC still needs to be explored. Methods: Data consisting of CDK7 expression levels, patient phenotypes and their matched survival were acquired from The Cancer Genome Atlas (TCGA) database. The associations of the CDK7 expression level with clinicopathological factors and cell proliferation were analyzed. The HCC transcriptome data in the GEO database were inquired and analyzed using GEO2R. Two representative HCC cell models were built to observe the proliferation capacity of HCC cells when CDK7 expression was inhibited by either shCDK7 or THZ1. Results: Based on the transcriptome and survival data in the TCGA database, the CDK7 expression level was inversely proportional to the overall survival of the HCC patients (pooled HR =1.51, 95% CI =1.06–2.15). For further investigation, the clinical features of HCC were integrated with the expression level of CDK7. A high expression of CDK7 was proportional to the survival time of the HCC patients (P=2.38×10−3), the neoplasm histologic grade (P